THE PRACTICE OF ELICITING TECHNIQUES IN EFL CLASSROOM INTERACTION (A DESCRIPTIVE STUDY OF TEACHERS' TECHNIQUES AT ONE OF THE SENIOR HIGH SCHOOL IN BANDUNG) - Mahmud Marzuki, - (2010)
The study entitled "The Practice of Eliciting Techniques in EFL Classroom Interaction" is aimed to investigate the types of eliciting techniques applied by the teachers to stimulate students' talk in the classroom interaction. It also identifies students' responses towards the teachers' eliciting techniques and the teachers' feedback to students' responses. The study was a qualitative research in which the study recorded the learning and teaching process. The participants of the study were two English teachers at one of the Senior High School in Bandung. There were four techniques to collect the data: classroom observation, video recording, field notes, and document analyses. The data analysis was carried out based on Suherdi's (2007) framework of classroom discourse analysis. To analyze the types of teachers' eliciting techniques, the study employed Coulthard (1975) and Slattery & Willis (2001) theories. The result of the study indicated that both of the teachers presented the materials were well organized and they succeed in activating the students to talk in the classroom interaction. They used a series of eliciting techniques in delivering the questions. From the overall of classroom observation, the teachers tended to apply eliciting inform in the form of questions using intonation only to stimulate students' talk. It was 87 (39.37%) from the total 221 eliciting techniques in the exchanges. It was a combination between two theories: Coulthard's (1975) and Slattery & Willis's (2001) theories. Relating to the students' responses, the students mostly used verbal word to respond the teachers' eliciting techniques (See Suherdi, 2006; 2007). It was 135 (70.68%) from the total 191 students' responses in the exchanges. In line with teachers' feedback, the teachers tended to give form-related comment feedback towards students' responses (See Lyster and Ratna, 1997). It was 40 (40.40%) from the total of 99 teachers' feedbacks in the exchanges. Finally, the study recommended for future researchers to do different analysis on the same subject such as identifying teachers' eliciting techniques in encouraging students talk and investigating how the teachers modify their words or questions through eliciting techniques to encourage students' talk. Key Words: Eliciting Techniques, Students' Talk, Classroom Interaction